The higher EAD market in Brazil: educommunicative practice and the social effects in the formation of democratic citizenship (Research, Society and Development, 2020)
In view of the expressive growth of Distance Education (EAD) in the last decade in Brazil, the present work aims to investigate some fragments about the social problem of higher education in the country through a study on the social context and on the propagation of this teaching modality, characterized as an application of educommunication. Based on this theme, we intend to promote the following question: what are the possible social effects generated by the spread of EAD as an educommunicative practice in the process of forming a democratic citizenship? For this purpose, a bibliographic research published by written and electronic means was carried out. Between the months of August and December 2019, in the electronic searches, the databases of Google Scholar, traditional Google, Scielo and Lilacs were accessed, aiming to collect information and previous knowledge about different positions regarding the investigated problem.